Dieu et ses appellations en vieux-saxon et en vieil-anglais - Thérèse Robin (Corela)
In this article we will compare the structure of nominal groups which refer to God in two texts written in 9th century, one in Old English (OE) and one in Old Saxon (OS). The terminology we use is the one of Jean Fourquet (1966, published in 2000/2001). Both Germanic languages are very close. The last text is considered as the original one. The first text is a translation of the OS one. What remains of both texts appears as fragments. In the remaining 25 common lines we will try to characterize the determination system of both languages between an old and a new system. We will take the whole fragments into account for this purpose. The way God is called is in both texts quite similar. The difference lies in the manner each language will take advantage of quite equivalent systems.